2017
DOI: 10.1371/journal.pone.0169076
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gray Matter Abnormalities in Idiopathic Generalized Epilepsy: A Meta-Analysis of Voxel-Based Morphology Studies

Abstract: ObjectiveWe aimed to identify the consistent regions of gray matter volume (GMV) abnormalities in idiopathic generalized epilepsy (IGE), and to study the difference of GMV abnormalities among IGE subsyndromes by applying activation likelihood estimation (ALE) meta-analysis.MethodsA systematic review of VBM studies on GMV of patients with absence epilepsy (AE), juvenile myoclonic epilepsy (JME), IGE and controls indexed in PubMed and ScienceDirect from January 1999 to June 2016 was conducted. A total of 12 IGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
1
25
0
1
Order By: Relevance
“…For the patients with JME, a significant gray matter volume increase is seen in medial frontal and anterior cingulate cortex, while significant gray matter decrease is found in pulvinar region. For the patients with AE, gray matter increase is found in thalamus, whereas gray matter decrease is revealed in subcallosal cortex, caudate nucleus, and precuneus [10]. However, this study did not investigate surface-based morphometry, such as cortical thickness, surface areas, or volumes in the patients with GGE, but only analyze the results of studies of voxelbased morphometry.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For the patients with JME, a significant gray matter volume increase is seen in medial frontal and anterior cingulate cortex, while significant gray matter decrease is found in pulvinar region. For the patients with AE, gray matter increase is found in thalamus, whereas gray matter decrease is revealed in subcallosal cortex, caudate nucleus, and precuneus [10]. However, this study did not investigate surface-based morphometry, such as cortical thickness, surface areas, or volumes in the patients with GGE, but only analyze the results of studies of voxelbased morphometry.…”
Section: Introductionmentioning
confidence: 98%
“…However, the structural differences in brain morphology among the different GGE syndromes are less well defined [6,8]. Only one study with applying activation likelihood estimation meta-analysis has showed that there are differences of gray matter volumes abnormalities among GGE subsyndromes [10]. For the patients with JME, a significant gray matter volume increase is seen in medial frontal and anterior cingulate cortex, while significant gray matter decrease is found in pulvinar region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abb. 1a; [1,2,14]) und in Diffusions-Tensor-Bildgebungs(DTI)-Untersuchungen Verände-rungen der thalamokortikalen Verbindungen des Frontallappens [12]. Diese Befunde wurden mittlerweile mehrmals repliziert [2], insbesondere bei der juvenilen myoklonischen Epilepsie (JME), dem häufigsten IGE-Syndrom.…”
Section: Strukturelle Mrt-befundeunclassified
“…Although the International League Against Epilepsy recognizes that GGEs characteristically have normal brain magnetic resonance imaging (MRI), studies for >2 decades have reported subtle brain abnormalities detected by quantitative neuroimaging techniques . Quantitative MRI studies in GGEs more often describe thalamic volume reduction in groups of individuals, although there are also descriptions of volume increase of the thalamus or no thalamic abnormality . Likewise, abnormalities of cortical and other subcortical structures vary in different studies .…”
mentioning
confidence: 99%